2011
DOI: 10.1111/j.1365-2966.2011.20136.x
|View full text |Cite
|
Sign up to set email alerts
|

The frequency of large variations in the near-infrared fluxes of T Tauri stars

Abstract: Variability is a characteristic feature of young stellar objects (YSOs) and could contribute to the large scatter observed in Hertzsprung–Russell (HR) diagrams for star‐forming regions. For typical YSOs, however, the long‐term effects of variability are poorly constrained. Here we use archived near‐infrared photometry from Two Micron All Sky Survey (2MASS), UKIDSS and DENIS to investigate the long‐term variability of high‐confidence members of the four star‐forming regions ρ‐Oph, ONC, IC348 and NGC 1333. The t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 42 publications
(61 reference statements)
3
41
0
Order By: Relevance
“…This view is supported by new survey results (e.g. [20,21]) that report frequent large luminosity variations in young forming stars.…”
Section: Ex Lupi and Other Exors: Extreme Versions Of A Larger Class?supporting
confidence: 53%
“…This view is supported by new survey results (e.g. [20,21]) that report frequent large luminosity variations in young forming stars.…”
Section: Ex Lupi and Other Exors: Extreme Versions Of A Larger Class?supporting
confidence: 53%
“…This object has been studied by Wilking et al (2005) who reported a SpT of M3.5 with no particular comments, only that there were strong emission lines in the spectrum. Scholz (2012) has also noted that this object is extremely variable in the near infrared, with variations up to ∼0.9 mag in K-band. The flux calibration of the spectrum analyzed here is compatible with the 2MASS photometry in J-and H-bands, and it was only correct by a factor 1.12 to account for slit losses to match these bands.…”
Section: A3 Iso−oph123mentioning
confidence: 85%
“…The total population of the surrounding Ophiucus region is estimated to be of around 300 YSOs , with ∼200 YSOs located in ρ-Oph itself. Given the large quantity of YSOs present in this cluster and its proximity, it has been extensively studied in the past at various wavelengths from optical, near-and far-infrared, millimeter, radio, to X-ray (e.g., Greene & Meyer 1995;Luhman & Rieke 1999;Wilking et al 2005;Alves de Oliveira et al 2010, 2012Bontemps et al 2001;McClure et al 2010;Gagné et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Rice et al (2012) have monitored the dark cloud L 1003 in Cygnus OB7 at NIR wavelengths with UKIRT over a time span of 1.5 years, and Morales et al (2011Morales et al ( , 2012 collected multi-epoch, multi-color light curves of candidate members of the Orion nebular cluster region during their dedicated Warm Spitzer Exploration Science Program YSOVAR (complemented by UKIRT and CFHT data). Likewise, a comprehensive longterm (meanwhile spanning 8 yrs) monitoring campaign of NIR variability in a large sample of brown dwarfs and T Tauri stars has been carried out by Scholz and collaborators (Scholz et al 2009;Scholz 2012).…”
Section: Introductionmentioning
confidence: 99%